2011
DOI: 10.1097/hp.0b013e3181f0cad5
|View full text |Cite
|
Sign up to set email alerts
|

Patient Safety and Electromagnetic Protection: A Review

Abstract: A systematic literature review was carried out to study patient security and possible harmful effects, immunity and interferences on medical devices, and effectiveness and transmission problems in healthcare and hospital environments due to electromagnetic interferences. The objective was to determine already-reported cases of patient security, immunity of medical devices, and transmission/reception failure in order to evaluate safety and security of patients. Literature published in the last 10 years has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…A general fear is still experienced regarding using the cell phone. A review has shown that they can disturb the functions of the pacemakers [33], although several studies have shown that today's cell phones do not interfere with the pacemakers implanted in the last 10 years, which means that the patients can feel entirely safe [34]- [36]. When the relatives dwindle situations that are perceived as inhibiting or limiting for the patient, it gives security in daring to living on as in the past, before the pacemaker implantation.…”
Section: Discussionmentioning
confidence: 99%
“…A general fear is still experienced regarding using the cell phone. A review has shown that they can disturb the functions of the pacemakers [33], although several studies have shown that today's cell phones do not interfere with the pacemakers implanted in the last 10 years, which means that the patients can feel entirely safe [34]- [36]. When the relatives dwindle situations that are perceived as inhibiting or limiting for the patient, it gives security in daring to living on as in the past, before the pacemaker implantation.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, the server shares the collected knowledge to the hospitals for more treatment. The server rings alarm to the auto X. bird genus et al [9] throughout emergency scenario. it's terribly helpful for elders and chronic patients World Health Organization need continuous observance.…”
Section: Literature Surveymentioning
confidence: 99%
“…The impacts of mobile phones with different frequency and UHF radio frequency receiver / transmitter on ventilators were examined in many statistical studies and a highly interaction was observed (Gilligan et al, 2000;PMDA, 2006;Lawrentschuk et al, 2004, Tan et al, 2001Bassen, 1998;FDA, 1997;Carranza et al, 2011;Pressly, 2000;Hans et al, 2008).…”
Section: Interactions Between Medical Devicesmentioning
confidence: 99%